Adsorption Site Selective Occupation Strategy within a Metal–Organic Framework for Highly Efficient Sieving Acetylene from Carbon Dioxide. (4th January 2021) - Yang, Lingzhi; Yan, Liting; Wang, Ying; Liu, Zhi; He, Jiangxiu; Fu, Qiuju; Liu, Dandan; Gu, Xin; Dai, Pengcheng; Li, Liangjun; Zhao, Xuebo
Abstract: The separation of acetylene and carbon dioxide is an essential but challenging process owing to the similar molecular sizes and physical properties of the two gas molecules. Notably, these molecules usually exhibit different orientations in the pore channel. We report an adsorption site selective occupation strategy by taking advantage of differences in orientation to sieve the C2 H2 from CO2 in a judiciously designed amine‐functionalized metal–organic framework, termed CPL‐1‐NH2 . In this material, the incorporation of amino groups not only occupies the adsorption sites of CO2 molecules and shields the interaction of uncoordinated oxygen atom and CO2 molecules resulting in a negligible adsorption amount and a decrease in enthalpy of adsorption but also strengthened the binding affinity toward C2 H2 molecules. This material thus shows an extremely high amount of C2 H2 at low pressure and a remarkably high C2 H2 /CO2 IAST selectivity (119) at 1 bar and 298 K. Abstract : Metal–organic framework (CPL‐1‐NH2 ) with keyhole‐like pore apertures offers selective adsorption site properties for gas separation. Amine groups limit interactions with CO2 molecules by decreasing the enthalpy of CO2 adsorption, whereas the binding affinity of C2 H2 is increased (see picture, distances in Å). CPL‐1‐NH2 demonstrates a remarkably high C2 H2 selectivity with C2 H2 /CO2 (50/50) mixtures at 1 bar and 298 K.